2017
DOI: 10.35818/acta.v10i2.379
|View full text |Cite
|
Sign up to set email alerts
|

Fishburger de Biquara (Haemulon Plumierii - Lacepède, 1801) com Adição de Diferentes Extensores

Abstract: <p>O objetivo do presente estudo foi elaborar <em>fishburger</em> de biquara (<em>Haemulon plumierii)</em> com intenção de agregar valor a uma espécie pesqueira pouco explorada utilizando diferentes porcentagens de agentes extensores: proteína texturizada de soja (PTS) -  1, 2 e 4% e amido de milho – 0, 1 e 2%, e avaliar aspectos físico-químicos (perda de peso na cocção, porcentagem de encolhimento, capacidade de retenção de água, cor objetiva e perfil de textura instrumental), nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Fay et al. (2015) explained that the difference in cooking loss (11.5% to 28%) between fish burgers lies in the contribution the corn starch gives to increase the WRC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fay et al. (2015) explained that the difference in cooking loss (11.5% to 28%) between fish burgers lies in the contribution the corn starch gives to increase the WRC.…”
Section: Resultsmentioning
confidence: 99%
“…The WRC is a product's ability to hold water contained in its structure, a technological factor used by the industry linked to the mass loss, quality and yield of meat products (Hautrive et al, 2008). Fay et al (2015) explained that the difference in cooking loss (11.5% to 28%) between fish burgers lies in the contribution the corn starch gives to increase the WRC.…”
Section: Characterization Of Tilapia Burger With Functional Agentsmentioning
confidence: 99%
“…Fernandes & Salas-Mellado (2017) described a similar result, as the authors claimed no change in the specific volume of bread and cakes with replacement of margarine by chia gel of up to 50%. Fay et al (2015) evaluated the use of different extenders in blue-striped grunt fishburger (Haemulon plumieri) and obtained weight losses ranging from 11.5 to 28%. Bainy et al (2015) found 85.3% yields in grilled tilapia fishburgers.…”
Section: Resultsmentioning
confidence: 99%
“…The low effect of the washing cycles on protein levels may be due to the addition of other ingredients into the formulation, such as soy protein isolate. Other authors also found no significant changes on protein levels (16.4%) of biquara (Haemulon plumierii) fishburger made with different proportions of textured soy protein (1%, 2%, and 4%) and corn starch (0%, 1%, and 2%) (Fay et al, 2015). Similar protein levels were found in different fish sausages, including Clarias slazera meat sausage (16.93%) (Ahmed & Elhaj, 2011), pasteurized sausage from MSM from Nile tilapia filleting residues (16.45%) (Dallabona et al, 2013); and fresh marine catfish sausage (Sciades herzbergii)…”
Section: Proximate Compositionmentioning
confidence: 91%